Soft X‐ray nanospectroscopy for quantification of X‐ray linear dichroism on powders - Hageraats, Selwin; Thoury, Mathieu; Stanescu, Stefan; Keune, Katrien (Journal of synchrotron radiation, 2021)
X‐ray linear dichroism (XLD) is a fundamental property of many ordered materials that can for instance provide information on the origin of magnetic properties and the existence of differently ordered domains. Conventionally, measurements of XLD are performed on single crystals, crystalline thin films, or highly ordered nanostructure arrays. Here, it is demonstrated how quantitative measurements of XLD can be performed on powders, relying on the random orientation of many particles instead of the controlled orientation of a single ordered structure. The technique is based on a scanning X‐ray transmission microscope operated in the soft X‐ray regime. The use of a Fresnel zone plate allows X‐ray absorption features to be probed at ∼40 nm lateral resolution – a scale small enough to probe the individual crystallites in most powders. Quantitative XLD parameters were then retrieved by determining the intensity distributions of certain diagnostic dichroic absorption features, estimating the angle between their transition dipole moments, and fitting the distributions with four‐parameter dichroic models. Analysis of several differently produced ZnO powders shows that the experimentally obtained distributions indeed follow the theoretical model for XLD. Making use of Monte Carlo simulations to estimate uncertainties in the calculated dichroic model parameters, it was established that longer X‐ray exposure times lead to a decrease in the amplitude of the XLD effect of ZnO. It is shown how soft X‐ray nanospectroscopy maps of powders (particle size ∼200 nm) can be analyzed to quantitatively retrieve X‐ray linear dichroism (XLD) parameters. A computational modeling procedure is described that can be used in conjunction with Monte Carlo simulations to prove statistical dissimilarity of XLD parameters between different samples.